Training curriculum to enhance the quality of life for the elderly - Charoenkiatkan, Chaloemchai; Khositditsayanan, Natthawat; Wannupatam, Benchaporn (Intelektual Pustaka Media Utama, 2024)
This study aimed to develop and evaluate a training curriculum intended to enhance the quality of life for the elderly. As Thailand witnesses a demographic shift with increasing numbers of older adults, driven by declining birth rates and extended life expectancies, the importance of ensuring quality elderly care becomes paramount. The devised curriculum encompasses eight principal elements focusing on the elderly, defined as those aged 60 and above, addressing their physical and mental changes, well-being, health, and overall satisfaction. The content is holistic, integrating components of music, art, health care, and exercise. Delivered over a two-day period, the curriculum employs a structured approach featuring lectures, discussions, and knowledge exchanges, supported by a range of media and materials. Initial assessments revealed a moderate quality of life among the elderly, but post-training evaluations indicated enhanced knowledge, understanding, and positive attitudes towards the activities, pointing to an overall high level of effectiveness of the curriculum.